the hardy boys mystery stories 35 : the clue in the embers - Dixon, Franklin W.; Franklin W. Dixon (Canada Grosset & Dunlap, Inc, 1955)
The Clue in the Embers (1955) is the 35th installment in The Hardy Boys Mystery Stories, following Frank and Joe Hardy as they help their friend Tony Prito recover stolen, valuable medallions from a newly inherited, bizarre curio collection. The investigation leads the brothers to Guatemala, where they battle a dangerous gang to find a hidden treasure.
English